A cross-sectional study to assess nutritional status among adolescents with disabilities in District Dehradun - Akash Krishali; Shaili Vyas; Abhay Srivastava; Neha Sharma (Journal of Family Medicine and Primary Care, 2025)
Background: Proper nutrition is vital for health and development. A lack of proper nutrition can lead to malnutrition, which is serious public health issue that can have lifelong consequences. Disabled children may have feeding difficulties, which can impact their nutrient intake. This study aims to assess the nutritional status of adolescents with disabilities using anthropometric measurements. Methodology: This research employed a school-based cross-sectional descriptive study design and focused on adolescents with disabilities attending special schools in Dehradun district. Nutritional status was evaluated through anthropometric measurements, including height, weight, and skinfold thickness. Results: A total of 142 study participants were included, with a mean age of 14.32 (±0.20) years. Notably, 93% of the study subjects had disabilities since birth, indicating congenital malformation. The majority of the participants, accounting for 52.1%, were classified as having a normal BMI, while 18.3% were categorized as overweight or obese. Conclusion: We found that the mental disability (38%) was the most common disability among adolescents. A relatively higher prevalence of underweight was seen in adolescent with hearing disability (47.8%).